Campesinato galo-romano na Antiguidade Tardia : um neodesenvolvimentismo? - Silva, Uiran Gebara da (2015)
This paper aims at evaluating the historiographical representations developed in the last decades, concerning the Later Roman countryside, with special regard to late antique Gaul. With the growth and expansion of the studies on rural archaeology in recent times, models postulating economic and commercial growth in the rural areas of the empire progressively replaced the previously held idea of a decadent Roman empire. Even though, the dynamical cores of the new models reside in Africa and Egypt, scholars have been proposing similar perspectives for other roman provinces. Taking into account the special case of late Roman north Gaul, this paper will focus on the discussion of some of the methods of investigation in which are based the results of this recent trend of Rural Archaeology: the role of survey archaeology in the discovery of sub-villa sites and the interpretation of these sites as local markets. Those models of economic growth have appeared in the context of a return to the modernist perspective in the study of Ancient Economy, based mainly in the use of New Institutional Economics as theoretical framing. Having that in mind, I render as problematic both that framing of the archaeological data and the application of capitalist criteria of growth and development for the Ancient World. Moreover, I try to draw from those new studies some suggestions on how to approach the archaeological data to create more complex and dynamic models of social and economic process than those the twentieth-century historiography offered to the understanding of late roman Gaul
O objetivo desse trabalho é avaliar as representaçoes historiográficas que se desenvolveram nas últimas décadas a respeito das regioes rurais do Império Romano, em particular na Gália tardo-antiga. Com o aumento e expansao do escopo da arqueologia rural nesse período, em substituiçao a uma visao de um Império em decadência, passou-se progressivamente a visoes que propoem crescimento econômico e comercial nas regioes rurais do Império. Muito embora os núcleos dinâmicos dessas visoes sejam a Africa e o Egito, propostas semelhantes estao sendo desenvolvidas para outras províncias, como a Gália. Observando o caso específico do norte da Gália tardo- romana, a avaliaçao dessas representaçoes busca refletir a respeito dos métodos de investigaçao nos quais se baseiam arqueologia rural, principalmente o papel da survey archaeology na produçao de sítios sub-villa e das interpretaçoes dos achados nesses sítios em termos da criaçao de mercados locais. Uma vez que essas perspectivas de crescimento econômico se dao no contexto também da reelaboraçao da perspectiva modernista no estudo da Economia Antiga por meio da aplicaçao da New Institutional Economics como enquadramento teórico, busca-se criticar parâmetros modernizantes de interpretaçao do quadro representado pela documentaçao material e problematizar o uso da ideia de desenvolvimento econômico inspirado em referências de desenvolvimento capitalista . Em contrapartida, busca-se propor formas de lidar com esse quadro documental de forma a elaborar modelos de processos sociais e econômicos mais complexos e dinâmicos do que a historiografia do século XX reconhecia para as regioes rurais da Gália tardo-romana^lpt
Keywords: Roman Gaul; Peasantry; Rural Archaeology; Local markets; Regionalization; Gália romana^lpt; Campesinato; Arqueologia Rural; Mercados Locais; Regionalizaçao